СПОСОБИ ПЕРЕКЛАДУ ЛЕКСИЧНИХ ОДИНИЦЬ В ОПОВІДАННЯХ ЗБІРКИ КАЗКИ РОБОТІВ СТАНІСЛАВА ЛЕМА: ПОЛЬСЬКО-УКРАЇНСЬКІ ПАРАЛЕЛІ. - Sytar, Hanna (Studia Interkulturowe Europy Środkowo-Wschodniej, 2024)
This article discusses the issues associated with the translation into Ukrainian of the collection of short stories Tales of Robots by Stanislav Lem. There are six translation methods used by professional translators: dictionary matching, transcoding, literal translation, contextual substitution, formal negation, and descriptive translation. Among the lexical transformations in the analysed translations, word extraction, and generalisation were recorded.The analysis of the language material allows us to distinguish two patterns. First, it is possible to state the consolidation of certain methods of translation for certain groups of vocabulary; in particular, the author's novelties are conveyed by using literal translation, whereby proper names are translated by the means of different subtypes of transcoding as well as literal translation. Second, the choice of translation method is often chosen considering not only the features of the source and target languages, but also using language intuition, "language taste", and craft of the translator.